2021
DOI: 10.35848/1347-4065/ac14a5
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-nanotube-based ultralight materials for ultrabroadband electromagnetic wave shielding and absorption

Abstract: In this paper, we report ultralight carbon-nanotube (CNT)-infused materials with high electromagnetic shielding and absorption performance over an ultrabroadband frequency range. By controlling the CNT content and thickness of ultralight aerogels composed of CNTs during fabrication, their electromagnetic shielding/absorbing performance can be tuned over a wide frequency range (5.6–110 GHz). Samples with 40 wt% CNTs exhibit excellent shielding performance in an intensity range of 30–90 dB in all frequency range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Conductive polymers such as polyaniline 39 and polypyrrole 40 are also widely used in constructing polymerbased metacomposites. Due to their diversity, high conductivity, wide application in supercapacitors, 41,42 energy storage materials 43,44 and other functional materials, [45][46][47][48] carbon materials exhibit great potential for building novel functionalized metacomposites. Efficient plasma oscillation can be achieved by constructing a carbon conductive network within the material.…”
Section: Regulation Strategies Of Carbonbased Metacompositesmentioning
confidence: 99%
“…Conductive polymers such as polyaniline 39 and polypyrrole 40 are also widely used in constructing polymerbased metacomposites. Due to their diversity, high conductivity, wide application in supercapacitors, 41,42 energy storage materials 43,44 and other functional materials, [45][46][47][48] carbon materials exhibit great potential for building novel functionalized metacomposites. Efficient plasma oscillation can be achieved by constructing a carbon conductive network within the material.…”
Section: Regulation Strategies Of Carbonbased Metacompositesmentioning
confidence: 99%
“…The hierarchical porous framework fabricated by a freeze-drying process using the growth of ice in the dispersion as a template produces ultralight and robust aerogels because it consists of strong SWCNT-CMC composite nanofiber networks. [32,33] The diameter of SWCNT-CMC composite nanofibers is smaller by more than an order of magnitude than that of microfibers fabricated by electrospinning, providing more opportunities for acoustic energy loss within the material. Furthermore, by confirming the consistency with the Biot-Johnson-Champoux-Allard (Biot-JCA) model, [34] which simultaneously considers the air-borne and solid-borne sound in the material, we showed that both the porous structure and elastic modulus of the framework of the ultralight SWCNT aerogel contribute to sound absorption.…”
Section: Introductionmentioning
confidence: 99%